Global burden of cardiovascular diseases: projections from 2025 to 2050 - Chong, Bryan; Jayabaskaran, Jayanth; Jauhari, Silingga Metta; Chan, Siew Pang; Goh, Rachel; Kueh, Martin Tze Wah; Li, Henry; Chin, Yip Han; Kong, Gwyneth; Anand, Vickram Vijay; Wang, Jiong-Wei; Muthiah, Mark; et al. (European journal of preventive cardiology, 2025)
The prediction of future trends in cardiovascular disease (CVD) mortality and their risk factors can assist policy-makers in healthcare planning. This study aims to project geospatial trends in CVDs and their underlying risk factors from 2025 to 2050. Using historical data on mortality and disability-adjusted life years (DALYs) from the Global Burden of Disease (GBD) 2019 study, encompassing the period of 1990 to 2019, Poisson regression was performed to model mortality and DALYs associated with CVD and its associated risk factors from 2025 to 2050. Subgroup analysis was based on GBD super-regions. Between 2025 and 2050, a 90.0% increase in cardiovascular prevalence, 73.4% increase in crude mortality, and 54.7% increase in crude DALYs are projected, with an expected 35.6 million cardiovascular deaths in 2050 (from 20.5 million in 2025). However, age-standardized cardiovascular prevalence will be relatively constant (-3.6%), with decreasing age-standardized mortality (-30.5%) and age-standardized DALYs (-29.6%). In 2050, ischaemic heart disease will remain the leading cause of cardiovascular deaths (20 million deaths) while high systolic blood pressure will be the main cardiovascular risk factor driving mortality (18.9 million deaths). Central Europe, Eastern Europe, and Central Asia super-region is set to incur the highest age-standardized cardiovascular mortality rate in 2050 (305 deaths per 100 000 population). In the coming decades, the relatively constant age-standardized prevalence of global CVD suggests that the net effect of summative preventative efforts will likely continue to be unchanged. The fall in age-standardized cardiovascular mortality reflects the improvement in medical care following diagnosis. However, future healthcare systems can expect a rapid rise in crude cardiovascular mortality, driven by the ageing global populace. The continued rise in CVD burden will largely be attributed to atherosclerotic diseases. Not applicable.